2021
DOI: 10.1371/journal.pone.0253180
|View full text |Cite
|
Sign up to set email alerts
|

Cyber-dating abuse in young adult couples: Relations with sexist attitudes and violence justification, smartphone usage and impulsivity

Abstract: Technologies have become important for interaction in couples. However, in some cases, controlling and aggressive behaviors can occur in the context of virtual interactions in couples; this is known as cyber-dating abuse (CDA). Identifying factors linked to CDA, as perpetrator and victim, are relevant for its prevention; therefore, more research is needed in this novel field of study. To contribute to the literature, our first goal was to analyze the associations among certain risk factors for CDA perpetration… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(30 citation statements)
references
References 56 publications
6
11
0
Order By: Relevance
“…Our results are in line with previous studies on CDA, which confirmed that control and direct aggression are common practices of CDA among young couples (Borrajo, Gámez‐Guadix, & Calvete, 2015; Borrajo, Gámez‐Guadix, Pereda, 2015; Lara, 2020; Linares et al., 2021; Taylor & Xia, 2018). Linares et al.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…Our results are in line with previous studies on CDA, which confirmed that control and direct aggression are common practices of CDA among young couples (Borrajo, Gámez‐Guadix, & Calvete, 2015; Borrajo, Gámez‐Guadix, Pereda, 2015; Lara, 2020; Linares et al., 2021; Taylor & Xia, 2018). Linares et al.…”
Section: Discussionsupporting
confidence: 92%
“…Our results are in line with previous studies on CDA, which confirmed that control and direct aggression are common practices of CDA among young couples Borrajo, Gámez-Guadix, Pereda, 2015;Lara, 2020;Linares et al, 2021;Taylor & Xia, 2018). Linares et al (2021) found that men realized that they were more controlling and aggressive than their female partners in the CDA context: they more commonly used insults and humiliation, displayed more sexist attitudes, and justified their violence.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…To this end, we constructed a serial mediational model between SNS addiction symptoms and BD (using the Body Shape Questionnaire [BSQ]; [ 68 ]), including awareness of appearance-related pressures and internalization of the thin ideal (using the Sociocultural Attitudes Towards Appearance Questionnaire-4 [SATAQ-4] awareness and internalization subscales; [ 69 ]) as mediating variables. Given the variety of SNSs used by college students, most of whom also use several SNSs (e.g., the majority of participants in Linares et al [ 70 ] used four or five SNSs), a scale to assess addiction to a specific SNS (e.g., the Bergen Facebook Addiction Scale; [ 29 ]) would have not been representative of all potential participants. Therefore, we used the Social Network Addiction scale (SNA; [ 71 ]) as a global measure of SNS addiction symptoms.…”
Section: Introductionmentioning
confidence: 99%